Advancement of lignin into bioactive compounds through selective organic synthesis methods - Jadhav, Pramod; Bhuyar, Prakash; Izan Izwan, Misnon; Mohd Hasbi, Ab Rahim; Rasidi, Roslan (Elsevier Ltd, 2024)
The conversion of lignin into bioactive compounds through selective organic synthesis methods represents a promising frontier in the pursuit of sustainable raw materials and green chemistry. This review explores the versatility of lignin-derived bioactive compounds, ranging from their application in drug discovery to their role in the development of biodegradable materials. Despite notable advancements, the synthesis routes and yields of highly bioactive molecules from lignin still require further exploration and improvement. This review provides an in-depth examination of the progress made in understanding the complex structure of lignin and developing innovative approaches to exploit its potential. Specifically, the types of lignins covered include softwood Kraft lignin, hardwood organosolv lignin, and soda lignin. This work is divided into three parts: first, the transformation of lignin into bioactive molecules with chemically active centres and functionalised hydroxyl groups through depolymerisation; second, kinetic modelling techniques essential for understanding the chemical kinetics of lignin and enabling significant scaling up in the conversion of organic molecules; third, efficient catalytic pathways for synthesising molecules with anticancer and antibacterial properties. In conclusion, this comprehensive review spurs further investigations into lignin-derived bioactive compounds, their applications, and the advancement of sustainable processes.